PENGAWETAN LIMA BELAS JENIS KAYU SECARA RENDAMAN PANAS-DINGIN DENGAN BAHAN PENGAWET BFCA - Sasa Abdurrohim; Barly Barly (Jurnal Penelitian Hasil Hutan, 1992)
Wood samples  of  15 species  measuring  5 x  5 x  30 cm  were treated  with 5 percent  of BFCA preservative by hot and cold  soaking.  Hot  soaking  period  was respectiuely 1  hour,  3 houn  and 5 hours, with  temperature  range  of 65ᵒC -  70ᵒ C, followed by  cold  soaking  for  24 hours. The  test  result  of  experiment, after taking  both  retention and penetration requirements into  consideration  for wood uses  under  roof,  and  in the  open  air both  without   ground  contact,  showed  that  nine Wood  species  could  be satisfactorily  treated  under   the  experimental  conditions.   However, it is important  to  note  that  one  of  the  nine species,  i.e.  benuang   (Octomeles   sumatrana)  fulfilled  the  requirements   for  wood   usage  under   the roof  only  without ground   contact.  The preservation schedule proposed  for  nine wood species is also presented in this paper.